2020
DOI: 10.1051/0004-6361/202038556
|View full text |Cite
|
Sign up to set email alerts
|

The orbit of Triton with new precise observations and the INPOP19a ephemeris

Abstract: Aims. The Gaia catalogue brings new opportunities and challenges to high-precision astronomy and astrometry. The precision of data reduction is therefore improved by a large number of reference stars with high-precision positions and proper motions. Numerous precise positions for Triton are obtained from the latest observations using the Gaia catalogue. Furthermore, the new INPOP19a planetary ephemeris, which also fits the observations from the Gaia Data Release 2, has recently become available. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…We also used about 40 differential coordinates of Triton from HST Additionally, we used the observations from Voyager 2 published by Jacobson (1991). These observations were also used in orbit determinations by Emelyanov & Samorodov (2015) and Tang et al (2020). The corresponding file vgr2-nep081.bsp 3 provides the positions of the Voyager 2 spacecraft that were used to calculate theoretical observations to compare with the measured data.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also used about 40 differential coordinates of Triton from HST Additionally, we used the observations from Voyager 2 published by Jacobson (1991). These observations were also used in orbit determinations by Emelyanov & Samorodov (2015) and Tang et al (2020). The corresponding file vgr2-nep081.bsp 3 provides the positions of the Voyager 2 spacecraft that were used to calculate theoretical observations to compare with the measured data.…”
Section: Observationsmentioning
confidence: 99%
“…Its motion is influenced by Neptune's oblateness and solar planet attractions. Other satellites of Neptune also affect Triton's motion, but the perturbations are rather small and exert negligible influence on its motion, as considered in Jacobson (2009), Emelyanov & Arlot (2011), Emelyanov & Samorodov (2015), and Tang et al (2020). Triton's orbit, however, is strongly influenced by the perturbations from the inner regular satellites of Neptune, as indicated by the NEP097 ephemeris reported by the NASA Jet Propulsion Laboratory (Brozović, priv.…”
Section: Orbital Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, Triton is often kept in its own category (Burns 1986b;Goldreich et al 1989). Jacobson (2009) and Tang et al (2020) both reported on the ephemeris of Triton.…”
Section: Introductionmentioning
confidence: 99%